Diagnosis and treatment of mental disorders – a review of the scientific literature - Pawłowski, Piotr; Brodowski, Wojciech; Borowik, Joanna; Swora, Aleksandra; Sygacz, Oliwer; Żelazny, Przemysław; Filipczak, Joanna; Dankiewicz, Sara; Bróż, Sebastian; Basta-Arciszewska, Katarzyna (Journal of Education, Health and Sport, 2022)
Introduction: Unambiguous definition of mental disorders is difficult, mainly because of the heterogeneity of this group of diseases and the clarity of the line between pathology and normal. The definition proposed by the World Health Organization (WHO) is widely accepted. In practice, definitions from the legislation of a country are also important. Aim of the work: The purpose of this study is to discuss the basic issues of diagnosis and treatment of mental disorders. Material and method: A method of non-systematic literature review from databases such as scientific Google Scholar, PubMed, CinalHl, Scopus, Arianta, Web of Science was used. Results and conclusions: In the treatment of mental disorders, I use pharmacological and non-pharmacological methods. Psychopharmaceuticals are divided into several groups depending on their mechanism of action. Their selection depends mainly on the diagnosed disease entity and tolerance to treatment. The most widely used group of drugs is the group of non-selective serotonin reuptake inhibitors (SSRIs). Non-pharmacological methods include psychotherapy, electroconvulsive therapy, deep brain stimulation, and psychosurgery.